Rabies Virus Hijacks and accelerates the p75NTR retrograde axonal transport machinery. - Shani Gluska (Public Library of Science (PLoS), 2014)
Rabies virus (RABV) is a neurotropic virus that depends on long distance axonal transport in order to reach the central nervous system (CNS). The strategy RABV uses to hijack the cellular transport machinery is still not clear. It is thought that RABV interacts with membrane receptors in order to internalize and exploit the endosomal trafficking pathway, yet this has never been demonstrated directly. The p75 Nerve Growth Factor (NGF) receptor (p75NTR) binds RABV Glycoprotein (RABV-G) with high affinity. However, as p75NTR is not essential for RABV infection, the specific role of this interaction remains in question. Here we used live cell imaging to track RABV entry at nerve terminals and studied its retrograde transport along the axon with and without the p75NTR receptor. First, we found that NGF, an endogenous p75NTR ligand, and RABV, are localized in corresponding domains along nerve tips. RABV and NGF were internalized at similar time frames, suggesting comparable entry machineries. Next, we demonstrated that RABV could internalize together with p75NTR. Characterizing RABV retrograde movement along the axon, we showed the virus is transported in acidic compartments, mostly with p75NTR. Interestingly, RABV is transported faster than NGF, suggesting that RABV not only hijacks the transport machinery but can also manipulate it. Co-transport of RABV and NGF identified two modes of transport, slow and fast, that may represent a differential control of the trafficking machinery by RABV. Finally, we determined that p75NTR-dependent transport of RABV is faster and more directed than p75NTR-independent RABV transport. This fast route to the neuronal cell body is characterized by both an increase in instantaneous velocities and fewer, shorter stops en route. Hence, RABV may employ p75NTR-dependent transport as a fast mechanism to facilitate movement to the CNS.